Jacques JOSET and Philippe RAXHON (editors): 1898-1998 Ends of Centuries. Hispanic American History and Literature. Brussels: Library of the Faculty of Philosophy and Letters of the Université de Liège, 2000, Fasciculo CCLXXIX, 191pp. (ALPHA. Journal of Arts, Literature and Philosophy, 2001)
No doubt the ends of the centuries are terrifying for some people; For others, however, they represent the almost metaphysical passage to another world, to a better future, to a new life, or a new story. The fact that the belief in awakening to a new history is accepted is a product of the teleological vision of temporality that, in our case, is not offered by Judeo-Christian culture, which leaves the passage from one life to another laid at its foundations.